The Electrical Behaviour Study on Saltwater Batteries in Various Electrolyte Concentrations and Cross-Sectional Areas - Anisa, Zuffa; Mubarokah, Lailatul; Rusdiana SE, Meilisa; Setyaningrum, Dyah (Hydrogen: Jurnal Kependidikan Kimia, 2025)
A study has been conducted to analyze the effect of various electrolyte concentrations and cross-sectional areas on voltage and current in batteries using the galvanic cell method (voltaic cells). This study aims to determine the electrolyte concentration and electrode cross-sectional area that provide optimal effects on voltage, current, and power in batteries. Variations in NaCl electrolyte concentration of 1 M; 3 M; 5 M; 7 M; and 9 M as electrolytes and variations in the cross-sectional area of Cu-Al 5 cm2, 10 cm2, 15 cm2, 20 cm2, 25 cm2 as electrodes. From these tests, the optimal voltage value was obtained at a concentration of 7 M and a cross-sectional area of 25 cm2 with a value of 0.73 V, the optimal current value at a concentration of 7 M and a cross-sectional area of 25 cm2 with a value of 19.99 mA, and the optimal power value at a concentration of 7 M and a cross-sectional area of 25 cm2 with a value of 14.593 mwatts. The larger the cross-sectional area of the electrode, the greater the electrical energy produced. The optimum concentration of electrolyte greatly influences the value of the electrical power produced.